2018
DOI: 10.4067/s0718-27242018000400061
|View full text |Cite
|
Sign up to set email alerts
|

Governance structure promoting innovation: an exploratory study in Brazilian habitats

Abstract: This research aimed to investigate how the governance structure of innovation habitats may contribute to the development of innovation in resident companies. An exploratory study was conducted in INOVAPARQ and CELTA incubator, in Brazil. The empirical contexts were investigated by applying qualitative method with NVivo software. Critical success factors of governance were found: managerial relationships with different stakeholders; national and international training networks; and boosted resident companies mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 59 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Not only they have insufficient knowledge on the true nature of innovations, but they are also unaware of the existing statistical tools and the EU initiatives they could use in their daily operations thus incentivizing possible changes within the governance of the whole EUSAIR macro-regional strategy. Kern Pipan et al (2012) claim that governance is an important factor for innovation generation, while Moré et al (2018) back this up by saying that efficient institutions and efficient decision-making result in higher degree of competitiveness. This research found that the AIR scores are low on the European Innovation Scoreboard.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only they have insufficient knowledge on the true nature of innovations, but they are also unaware of the existing statistical tools and the EU initiatives they could use in their daily operations thus incentivizing possible changes within the governance of the whole EUSAIR macro-regional strategy. Kern Pipan et al (2012) claim that governance is an important factor for innovation generation, while Moré et al (2018) back this up by saying that efficient institutions and efficient decision-making result in higher degree of competitiveness. This research found that the AIR scores are low on the European Innovation Scoreboard.…”
Section: Discussionmentioning
confidence: 99%
“…Financial incentives, however, are not the only factor fostering innovations. Governance is found to be an important factor for innovation generation (Kern Pipan et al, 2012) since "slow institutions and lengthy decision-making processes involve less innovative and less degree of competitiveness" (Moré et al, 2018). These were the starting points of this research.…”
Section: Introductionmentioning
confidence: 96%
“…Interactions with external partners are made through informal and formal processes, sometimes through a physical space (Moré et al, 2018). The Hub also facilitates informal relationships and ongoing knowledge exchange between the corporation and external partners, as well as between the partners themselves.…”
Section: Corporate Innovation Hubsmentioning
confidence: 99%
“…However, the results presented in Chapter 4 indicate how that Hub can evolve into an Orchestrator while increasingly becoming accountable for radical innovations by influencing the mainstream to lead the incremental innovations (like internal process improvement). Furthermore, another research stream is responsible for presenting a governance structure for the innovation hub mechanisms concerning mechanisms for innovation management, engagement with ecosystems, and hub-mainstream integration (Moré et al, 2018;Remneland Wikhamn & Styhre, 2019). Nevertheless, it does not consider an evolutionary process of the Hub explaining how the mechanisms' governance integrates into the corporate hub evolution: how and when this governance surges and how it connects to the Hub's mandate, orientation, and identity.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation